THU0261 Outcomes in Systemic Lupus Erythematous (SLE) Patients with High Disease Activity Treated with Belimumab: Results from an Observational Study in the United States (U.S.). (23rd January 2014) - Kan, H.; Collins, C.; Dall'Era, M.; McGuire, M. B.; Koscielny, V.; Pappu, R.; Molta, C.
Abstract : Background: Post hoc analyses of belimumab BLISS trials identified baseline factors generally associated with high disease activity as predictors of improved response to treatment, such as SELENA-SLEDAI (SS)> 10, low complement levels, anti-dsDNA positivity and glucocorticoid therapy. Objectives: We examined clinical outcomes in patients with high disease activity treated with belimumab in U.S. clinical practice settings in 2012. Methods: OBSErve (BLM117295) is a multicenter retrospective medical chart review study. 92 rheumatologists from U.S. non-academic centers who treat >10 SLE patients annually and have >5 years of practice experience were randomly recruited. Physicians randomly identified adult SLE patients who had received ≥8 infusions of belimumab as part of usual-care. Index date is the first belimumab infusion date. This post-hoc analysis was conducted among patients with low complement and high anti-dsDNA, steroids ≥7.5mg/day, and SS>10 at index date. Results were reported for the 3 subgroups and the entire sample. The primary outcome was the change in overall SLE disease manifestations 6 months after index date based on physician judgement. Changes from index date in SS and oral steroid dose (when available at index date) were also analyzed. Results: 501 eligible patient charts were abstracted. Key patient characteristics at index date were mean age 41.3 yrs; female 89%; Caucasian 53%, black/African American 24%, Hispanic 18%; and SLE disease duration≤5yrs 56%. 50% (n=252) had hypocomplementemia and high anti-dsDNA, 69% (n=347) had steroid dose≥7.5mg/day, and 86 (70%) out of 122 with available SS had SS>10 at index date. Physician impression of overall change in disease manifestations over 6 months was similar in the subgroups of high disease activity compared to the entire sample. Within the 3 subgroups, mean SS scores decline ranged from 6.8-7.5 (51-53%), and mean steroid reduction ranged from 11.5-15.0 mg/day (58-61%) over 6 months. Conclusions: Among the SLE patients with markers of high disease activity treated with at least 6 months of belimumab in clinical practice settings, clinicians observed improvement in overall SLE clinical manifestations, reduction in SELENA-SLEDAI, and reduction in steroid dose 6 months after belimumab initiation with no control arm. Disclosure of Interest: H. Kan Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Collins Consultant for: GlaxoSmithKline, M. Dall'Era Consultant for: GlaxoSmithKline, M. McGuire Grant/research support from: GlaxoSmithKline, V. Koscielny Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, R. Pappu Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Molta Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline